Mutasi Sinar Gamma untuk Meningkatkan Kandungan Metabolit Sekunder dan Analisis Isozim Jamur Tiram - Ira Djajanegara; Retno Lestari; Harsoyo Harsoyo; Priyo Wahyudi (Fakultas Farmasi Universitas Pancasila, 2004)
Oyster mushroom (Pleurotus ostreatus) is one of the commonly consumed mushrooms due to its nutritious as well as its pharmaceutical value. It has been known that this mushroom contains several substances such as interferon inducer to help prevent several diseases i.e. hepatitis and many others. There are three cultivars of oyster mushroom based on the color of their fruit body, namely white oyster mushroom (Pleurotus floridae), grey oyster mushroom (Pleurotus sajur-caju) and brown oyster mushroom (Pleurotus cystidious). A possibility to increase its phamaceutical value is mutation using Gamma ray. The doses of mutation used are 0.25 KGy, 0.5 KGy, 0.75 KGy, and 1.0 KGy respectively. Since most of the pharmaceutical substances are secondary metabolite products of this mushroom, the mutation is intended to increase these metabolites. In this preliminary experiment, the mutation process is observed using isozyme analysis of the mutated mycelia as the indicator.